EFFICIENCY OF DIFFERENTIATED INSTRUCTION IN DEVELOPING STUDENTS’ PAREMIOLOGICAL COMPETENCE (Scientific journal of the Fergana State University, 2023)
This article is devoted to the efficiency of differentiated education in developing students' paremiological competence. Based on difficulty level of proverbs and sayings it is recommended improving students’ paremiological competence through different methods and techniques, including discussion, synonyms, scrambled proverb quiz by using mobile application Telegram as well as applying Foyer Model to consolidate learners’ awareness.